Gênero, raça e pós-graduação: um estudo sobre a presença de mulheres negras nos cursos de mestrado da Universidade Federal Fluminense - Pinto, Giselle (2008)
This work presents the racial and gender profiles of the Fluminense Federal University Program of Postgraduate Studies considering the Maters Degree course throughout the period of 2004 2006. Subsequent to the identification of this profile, the presence of black women in the post- graduation of this University is traced. Black women life trajectories are analyzed through specific methodology in order to verify the influence of gender and race in the Masters program. Quantitative and qualitative data were collected: the former was obtained through the University Program of Postgraduate Studies coordination considering the Arts, Humanities, Mathematical Sciences and Technology areas. The qualitative data were collected through interviews with black women of the referred areas. In general terms, the data indicate the existence of inequalities of participation between men and women, whites and blacks, in Maters Degree course of this University. Thus, the conclusion shows that the black women, besides their constant struggle, still benefit little from the advantages conquered by the white women through the feminist movement claims. In addition, the presented trajectories reveal that the black women need to develop a number of strategies to enter the academic space and to obtain social conditions similar to the whites.